Adhesive sheet and method for recycling adhesive sheet
By introducing an alcohol-soluble or water-soluble resin separation layer into the adhesive sheet, the environmental load problem during the recirculation of the adhesive sheet is solved, safe and efficient separation and reuse are achieved, and the range of adhesive selection is expanded.
Patent Information
- Application Number
- CN202480005750.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-06
- Filing Date
- 2024-02-07
- Publication Date
- 2025-08-12
Smart Images

Figure CN120476184A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive sheet and a method for recycling the adhesive sheet. Background Art
[0002] PSA sheets are widely used for attaching labels, etc., to articles and packaging materials, for packaging materials, in the manufacturing process of electronic and optical components, and for masking purposes. In recent years, in particular, the use of PSA sheets in the manufacturing process of electronic and optical components has increased, and the environmental impact caused by the disposal of PSA sheets has become a problem.
[0003] Adhesive sheets are typically composed of adhesives and substrates, and research is underway to separate these components and reuse them as a means of reducing environmental load. For example, a method has been proposed to dissolve and remove components other than the substrate using an alkaline solution. However, this method has the following problems: it requires strong alkaline water and is therefore dangerous; it is necessary to consider the corrosion resistance of the equipment; it requires a long time and high energy; and sometimes the substrate deteriorates. In addition, a method has been proposed to separate the components other than the substrate by grinding (Patent Document 1). However, this method has problems such as complicated procedures and a narrow range of applications. As such, conventional adhesive sheets have had problems with recyclability, and an adhesive sheet with excellent recyclability that can solve various problems is being sought.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2022-130226 Summary of the Invention
[0007] Problems to be solved by the invention
[0008] An object of the present invention is to provide a PSA sheet having excellent recyclability.
[0009] Solutions for solving problems
[0010] [1] The pressure-sensitive adhesive sheet according to an embodiment of the present invention includes, in this order, a pressure-sensitive adhesive layer, a separation layer, and a base material formed of a resin, wherein the separation layer is composed of an alcohol-soluble resin or a water-soluble resin.
[0011] [2] In the adhesive sheet described in [1] above, the anchoring force A of the adhesive sheet may be 1 N / 20 mm or more.
[0012] [3] In the PSA sheet of [1] or [2] above, the ratio of the anchoring force A of the PSA sheet to the adhesive force A of the PSA sheet may be 2 or greater.
[0013] [4] In the PSA sheet according to any one of [1] to [3] above, the ratio of the anchoring force A of the PSA sheet to the anchoring force B of a sample sheet without the separation layer may be 0.5 or greater.
[0014] [5] In the adhesive sheet described in any one of [1] to [4] above, the anchoring force C after immersing the adhesive sheet in water at 23° C. for 30 minutes may be 1 N / 20 mm or greater.
[0015] [6] In the PSA sheet described in any one of [1] to [5] above, the ratio of the anchoring force C after immersing the PSA sheet in water at 23° C. for 30 minutes to the anchoring force A of the PSA sheet may be 0.5 or greater.
[0016] [7] In the PSA sheet according to any one of [1] to [6] above, the PSA sheet may have an adhesive strength A of 0.7 or greater relative to an adhesive strength B of a sample sheet without the separation layer.
[0017] [8] In the pressure-sensitive adhesive sheet according to any one of [1] to [7] above, the separation layer may be composed of an alcohol-soluble resin.
[0018] [9] In the adhesive sheet described in any one of [1] to [8] above, the alcohol-soluble resin may be a polyamide resin, an aminoethylated polymer resin, a polyvinyl butyral resin, a polyvinyl pyrrolidone resin, or an oxazoline group-containing polymer resin.
[0019]
[10] In the pressure-sensitive adhesive sheet according to any one of [1] to [9] above, the separation layer may contain a resin having a cross-linked structure.
[0020]
[11] In the pressure-sensitive adhesive sheet according to any one of [1] to
[10] above, the separation layer may have a thickness of 0.01 μm to 5 μm.
[0021]
[12] In the pressure-sensitive adhesive sheet according to any one of [1] to
[11] above, the substrate may be composed of a polyester resin or a polyolefin resin.
[0022]
[13] In the pressure-sensitive adhesive sheet according to any one of [1] to
[12] above, the substrate may be a surface-treated substrate.
[0023]
[14] In the pressure-sensitive adhesive sheet according to any one of [1] to
[13] above, the pressure-sensitive adhesive layer may contain an acrylic pressure-sensitive adhesive.
[0024]
[15] In the pressure-sensitive adhesive sheet according to any one of [1] to
[14] above, the pressure-sensitive adhesive layer may contain an emulsion-based pressure-sensitive adhesive.
[0025]
[16] In the adhesive sheet described in any one of [1] to
[15] above, the adhesive layer and the substrate are separable using a solvent that can dissolve the resin constituting the separation layer.
[0026]
[17] A method for recycling a PSA sheet according to an embodiment of the present invention includes impregnating the PSA sheet according to any one of [1] to
[16] above and including a PSA layer containing an alcohol-soluble resin in an alcohol solution.
[0027]
[18] A method for recycling an adhesive sheet according to an embodiment of the present invention includes impregnating an adhesive sheet according to any one of [1] to
[16] above and having an adhesive layer containing a water-soluble resin in an aqueous solution.
[0028]
[19] The laminate according to the embodiment of the present invention includes a functional layer, a separation layer, and a substrate in this order, and the separation layer is composed of an alcohol-soluble resin.
[0029] Effects of the Invention
[0030] According to the present invention, a PSA sheet having excellent recyclability can be provided by providing a predetermined separation layer between the substrate and the PSA layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. DETAILED DESCRIPTION
[0032] A. Overview of PSA Sheet
[0033] Figure 1 This is a schematic cross-sectional view of an adhesive sheet according to one embodiment of the present invention. The adhesive sheet 100 sequentially comprises an adhesive layer 10, a release layer 20, and a substrate 30. The release layer 20 is composed of an alcohol-soluble resin or a water-soluble resin. The substrate 30 is formed of a resin. Although not shown, the adhesive sheet may further comprise any other suitable layers as long as the effects of the present invention are achieved. For example, a release liner may further be provided to protect the adhesive layer prior to use.
[0034] According to an embodiment of the present invention, there is provided an adhesive sheet which, by having a separation layer composed of an alcohol-soluble resin or a water-soluble resin, can separate the adhesive layer and the substrate using a solvent that dissolves the resin constituting the separation layer. The separated elements can be reused. The adhesive sheet of an embodiment of the present invention is advantageous in that it can be recycled through a simple and safe operation. In addition, it is also advantageous in that the range of choices of the adhesive constituting the adhesive layer is wide. In one embodiment, the adhesive sheet is an adhesive sheet having a separation layer composed of an alcohol-soluble resin, and the substrate and the adhesive layer can be separated by impregnation in an alcohol solution. In another embodiment, the adhesive sheet is an adhesive sheet having a separation layer composed of a water-soluble resin, and the substrate and the adhesive layer can be separated by impregnation in water.
[0035] The anchoring force A of the above-mentioned adhesive sheet is preferably 1N / 20mm or more, more preferably 3N / 20mm or more, further preferably 8N / 20mm or more, particularly preferably 10N / 20mm or more. When it is such a range, it is possible to obtain an adhesive sheet that fully utilizes the function of the adhesive sheet. For example, it is possible to obtain an adhesive sheet that can prevent unnecessary interlayer peeling during use. The higher the anchoring force A of the above-mentioned adhesive sheet, the more preferred it is, and its upper limit is, for example, 25N / 20mm (preferably 20N / 20mm). In this specification, the anchoring force is the peeling force when peeling the adhesive layer from the substrate. The anchoring force is measured as follows: For the adhesive sheet, an adhesive tape A (manufactured by Nitto Denko Corporation, trade name "No. 315", thermosetting rubber-based adhesive, polyester film peeling adhesion 14.8 (N / 19mm)) is laminated on the above-mentioned adhesive sheet in such a manner that the adhesive layer of the adhesive tape A is opposite to the adhesive layer of the above-mentioned adhesive sheet, and the obtained laminate is subjected to a tensile test (measurement temperature: 23°C, peeling speed: 300mm / min, peeling angle: 180°), and the adhesive tape A is peeled off from the above-mentioned adhesive sheet, thereby measuring (details are described later). It should be noted that, in the measurement of the anchoring force, the peeling position is not limited. Therefore, the peeling position when measuring the anchoring force A can be the interface of each layer, or it can be peeling caused by damage within each layer. The above-mentioned anchoring force can be adjusted by, for example, the composition of each layer, the surface treatment of the substrate, etc.
[0036] The adhesive force A of the above-mentioned adhesive sheet is preferably 0.01N / 20mm~100N / 20mm, more preferably 0.02N / 20mm~50N / 20mm, and further preferably 0.05N / 20mm~30N / 20mm. When it is in such a range, an adhesive sheet that can well hold the adherend can be obtained. In this specification, the adhesive force refers to the adhesive force at 23°C when the adhesive layer is attached to a SUS304 plate. The adhesive force is measured in accordance with JIS Z0237:2000. Specifically, the adhesive sheet is attached to a SUS304 plate (arithmetic mean surface roughness Ra: 50±25nm) by moving a 2kg roller back and forth once, and after leaving it at 23°C for 30 minutes, the adhesive sheet is peeled off under the conditions of a peeling angle of 180° and a peeling speed (tensile speed) of 300mm / min for measurement.
[0037] The ratio of the anchoring force A to the adhesive force A is preferably 2 or greater, more preferably 5 or greater, even more preferably 10 to 500, particularly preferably 10 to 100, and most preferably 10 to 50. Within this range, a PSA sheet that fully demonstrates its function as a PSA sheet can be obtained. For example, a PSA sheet having a preferred adhesive force can be obtained while preventing unnecessary interlayer delamination (adhesive residue) during use.
[0038] The ratio of the anchoring force A to the anchoring force B of the sample sheet formed without a separation layer is preferably 0.5 or more, more preferably 0.7 or more, and further preferably 0.9 or more. In one embodiment, the ratio of the anchoring force A to the anchoring force B is 1 or more, preferably 1.5 or more. In one embodiment, by providing a separation layer, the anchoring force of the adhesive sheet can be improved. In one embodiment, when an adhesive layer containing an aqueous adhesive is provided, such an effect becomes significant. The higher the upper limit of the ratio of the anchoring force A to the anchoring force B, the more preferred it is, for example, 100 (preferably 200). In one embodiment, the upper limit of the ratio of the anchoring force A to the anchoring force B is, for example, 2.5, preferably 3. The "sample sheet formed without a separation layer" is a sheet obtained by excluding the separation layer from the adhesive sheet for measuring the anchoring force A, and is a sheet having the same substrate and adhesive layer as the substrate and adhesive layer of the adhesive sheet for measuring the anchoring force A.
[0039] The anchoring force C after immersing the PSA sheet in water at 23°C for 30 minutes is preferably 1 N / 20 mm or greater, more preferably 4 N / 20 mm or greater, even more preferably 8 N / 20 mm or greater, and particularly preferably 10 N / 20 mm or greater. Within this range, a PSA sheet with excellent water resistance can be obtained. A higher anchoring force C is preferred, with an upper limit of, for example, 20 N / 20 mm (preferably 40 N / 20 mm).
[0040] The ratio of the anchoring force C to the anchoring force A is preferably 0.5 or greater, more preferably 0.7 or greater, and even more preferably 0.9 or greater. Within this range, a PSA sheet with excellent water resistance can be obtained. The upper limit of the ratio of the anchoring force C to the anchoring force A is, for example, 1, preferably 1.2.
[0041] The ratio of the above-mentioned adhesive force A to the adhesive force B of the sample sheet formed without a separation layer is preferably 0.7 or more, more preferably 0.9 or more. When it is within this range, it is possible to obtain an adhesive sheet that prevents the transfer of components from other layers to the adhesive layer, thereby preferably exhibiting adhesive force. The upper limit of the ratio of the anchoring force to the anchoring force B is, for example, 1, preferably 1.2. The "sample sheet formed without a separation layer" is a sheet obtained by excluding the separation layer from the adhesive sheet for measuring the adhesive force A, and is a sheet having the same substrate and adhesive layer as the adhesive sheet for measuring the adhesive force A.
[0042] The thickness of the pressure-sensitive adhesive sheet is preferably 1 μm to 300 μm, more preferably 5 μm to 200 μm.
[0043] In one embodiment, the adhesive layer can be replaced by a functional layer. In one embodiment, a laminate is provided which sequentially comprises a functional layer, a separation layer, and a substrate. Preferably, the separation layer contained in the laminate is composed of an alcohol-soluble resin. In one embodiment, the substrate can be formed of a resin. The functional layer is a layer having a prescribed function, and its composition is not particularly limited. For example, in addition to the adhesive layer, the functional layer may include a hard coat layer, an adhesive layer, a release layer, a decorative layer, a light-shielding layer, an ultraviolet shielding layer, an easy-adhesion layer, and the like.
[0044] B. Adhesive layer
[0045] The adhesive layer includes any appropriate adhesive. As the adhesive constituting the adhesive layer, any appropriate adhesive can be used as long as the effect of the present invention can be brought into play. As the adhesive, for example, acrylic adhesives, silicone adhesives, vinyl alkyl ether adhesives, polyester adhesives, polyamide adhesives, urethane adhesives, fluorine adhesives, styrene-diene block copolymer adhesives, active energy ray curing adhesives, etc. can be cited. In one embodiment, an acrylic adhesive is used. In addition, the adhesive can be an emulsion adhesive. In an embodiment of the present invention, by having a separating layer, it is possible to provide a kind of adhesive sheet that can cope with a variety of adhesives and has high recyclability.
[0046] In one embodiment, the adhesive layer comprises a water-based adhesive. A water-based adhesive is an adhesive in which adhesive components are contained in a solvent containing water (aqueous solvent). In an embodiment of the present invention, the adhesive layer may be formed by applying a water-based adhesive.
[0047] Examples of the acrylic pressure-sensitive adhesive include those using, as a base polymer, an acrylic polymer (homopolymer or copolymer) containing one or two or more (meth)acrylate esters as monomer components. Specific examples of the alkyl (meth)acrylate include C1-20 alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. Among these, alkyl (meth)acrylates having a linear or branched alkyl group having 4 to 18 carbon atoms can be preferably used.
[0048] For the purpose of improving cohesion, heat resistance, crosslinking properties, etc., the acrylic polymer may contain units corresponding to other monomers copolymerizable with the alkyl (meth)acrylate as needed. Examples of such monomers include carboxyl group-containing monomers such as acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid; acid anhydride monomers such as maleic anhydride and itaconic anhydride; hydroxyl group-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl methacrylate; styrenesulfonic acid, allylsulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylic acid Sulfonic acid group-containing monomers such as amidopropanesulfonic acid, sulfopropyl (meth)acrylate, and (meth)acryloyloxynaphthalenesulfonic acid; (N-substituted)amide monomers such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxymethylpropane (meth)acrylamide; (meth)acrylic acid aminoalkyl ester monomers such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; (meth)acrylic acid alkoxyalkyl ester monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; N- Maleimide monomers such as cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide; succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; vinyl acetate, vinyl propionate, and N - Vinyl monomers such as vinyl pyrrolidone, methyl vinyl pyrrolidone, vinyl pyridine, vinyl piperidone, vinyl pyrimidine, vinyl piperazine, vinyl pyrazine, vinyl pyrrole, vinyl imidazole, vinyl oxazole, vinyl morpholine, N-vinyl carboxylic acid amides, styrene, α-methylstyrene, and N-vinyl caprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy group-containing acrylic monomers such as glycidyl (meth)acrylate; glycol acrylate monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate;Acrylate monomers having heterocyclic rings, halogen atoms, silicon atoms, etc., such as tetrahydrofurfuryl (meth)acrylate, fluoro(meth)acrylate, and silicone (meth)acrylate; polyfunctional monomers such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate; olefin monomers such as isoprene, butadiene, and isobutylene; and vinyl ether monomers such as vinyl ether. These monomers may be used alone or in combination of two or more.
[0049] Examples of the emulsion-based adhesive include acrylic adhesives, and rubber-based adhesives based on natural rubber latex, styrene-butadiene rubber latex, etc. These can constitute the emulsion-based adhesive in the form of a water dispersion.
[0050] Rubber-based adhesives include, for example, adhesives based on rubber-based polymers such as natural rubber, styrene-isoprene-styrene block copolymers, styrene-butadiene-styrene block copolymers, styrene-ethylene-butylene-styrene block copolymers, styrene-butadiene rubber, polybutadiene, polyisoprene, polyisobutylene, butyl rubber, chloroprene rubber, and silicone rubber. Aqueous dispersions of these polymers can be obtained as natural products such as natural rubber latex by emulsion polymerization or post-emulsification of the resulting polymers.
[0051] (additive)
[0052] The adhesive may contain any appropriate additives as needed. Examples of such additives include crosslinking agents, tackifiers, plasticizers, emulsifiers, viscosity modifiers, pigments, dyes, fillers, antioxidants, conductive materials, antistatic agents, ultraviolet absorbers, light stabilizers, release modifiers, softeners, surfactants, flame retardants, antioxidants, foaming agents, particles, photopolymerization initiators, crosslinking retarders, catalysts, and the like.
[0053] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, and peroxide crosslinking agents, as well as urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, and amine crosslinking agents. Among these, an isocyanate crosslinking agent, an epoxy crosslinking agent, or a carbodiimide crosslinking agent is preferred.
[0054] Specific examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "CORONATE L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "CORONATE HL"), isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industry Co., Ltd., trade name "CORONATE XL"); HX”); etc. The content of the isocyanate crosslinking agent can be set to any appropriate amount according to the desired adhesive strength, elasticity of the adhesive layer, etc., and is typically 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, relative to 100 parts by weight of the base polymer.
[0055] Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "Tetrad C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Epolight 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Epolight 1500NP"), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Epolight 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "Epolight 70P"), polyethylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name "EPIOL E-400”), polypropylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name “EPIOL P-200”), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “Denacol EX-611”), glycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “Denacol EX-314”), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX Corporation, trade name “Denacol EX-512”), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycidyl adipate, diglycidyl phthalate, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, epoxy resins having two or more epoxy groups in the molecule, and the like. The content of the epoxy crosslinking agent can be set to any appropriate amount depending on the desired adhesive strength, elasticity of the adhesive layer, etc., and is typically 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, per 100 parts by weight of the base polymer.
[0056] The thickness of the adhesive layer is preferably 1 μm to 300 μm, more preferably 2 μm to 250 μm, further preferably 3 μm to 100 μm, and particularly preferably 5 μm to 60 μm.
[0057] C.Substrate
[0058] Above-mentioned substrate is made up of any appropriate resin.As the resin constituting substrate, for example, can enumerate acrylic resins such as polyimide (PI), polyetheretherketone (PEEK), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polymethyl methacrylate (PMMA), polycarbonate, cellulose triacetate (TAC), polysulfone, polyarylate, polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, ethylene-vinyl acetate copolymer (EVA), polyamide (nylon), fully aromatic polyamide (aramid), polyvinyl chloride (PVC), polyvinyl acetate, polyphenylene sulfide (PPS), fluorine-based resin, cyclic olefin resin etc..Preferably use the resin that is insoluble (insoluble) in alcohol.In 1 embodiment, above-mentioned substrate is made up of polyester resin or polyolefin resin (preferably polypropylene resin).
[0059] The thickness of the substrate is preferably 1 μm to 500 μm, more preferably 5 μm to 300 μm, and even more preferably 10 μm to 100 μm.
[0060] The substrate may be surface treated. Surface treatment can be used to adjust the anchoring force. Examples of surface treatments include corona treatment, chromic acid treatment, ozone exposure, flame exposure, high-voltage electric shock exposure, ionizing radiation treatment, and primer-based coating.
[0061] D. Separation layer
[0062] As described above, the separation layer is composed of an alcohol-soluble resin or a water-soluble resin.
[0063] In this specification, an alcohol-soluble resin refers to a resin that is soluble in alcohol, and for example, it may be a resin that is soluble in 1% by weight or more of an alcohol (e.g., an alcohol having 1 to 4 carbon atoms) at a temperature of 60°C or lower. Furthermore, a water-soluble resin refers to a resin that is soluble in water, and for example, it may be a resin that is soluble in 1% by weight or more of water at a temperature of 60°C or lower.
[0064] In one embodiment, the separation layer is composed of an alcohol-soluble resin. If such a separation layer is formed, a water-based adhesive can be applied by coating, preferably forming an adhesive layer. In addition, an adhesive sheet with excellent moisture resistance can be obtained.
[0065] As the alcohol-soluble resin, for example, polyamide resins, polyvinyl pyrrolidone resins, aminoethylated polymer resins, polyvinyl butyral resins, polyvinyl formal resins, polyvinyl acetal resins such as partially acetalized polyvinyl acetal resins obtained by modifying a portion of butyral with methylal, acetal, etc., cellulose resins, polyvinyl phenol resins, oxazoline-containing polymer resins, etc. are mentioned. Among them, polyamide resins, aminoethylated polymer resins, polyvinyl butyral resins, polyvinyl pyrrolidone resins, or oxazoline-containing polymer resins are preferred. Polyvinyl butyral resins, polyvinyl pyrrolidone resins, polyamide resins, or aminoethylated polymer resins are more preferred.
[0066] When the separation layer contains an alcohol-soluble resin, the content of the alcohol-soluble resin is preferably 50 parts by weight or more, more preferably 80 parts by weight or more, and even more preferably 90 parts by weight or more per 100 parts by weight of the separation layer. In one embodiment, the separation layer is composed solely of the alcohol-soluble resin.
[0067] Examples of the water-soluble resin include polyvinyl pyrrolidone resins, polyvinyl alcohol resins, and polyethyleneimine resins. Polyvinyl butyral resins are obtained by reacting polyvinyl alcohol with butyraldehyde to form butyrals of the hydroxyl groups of polyvinyl alcohol resins, and are composed of a vinyl butyral portion, a vinyl alcohol portion, and a vinyl acetate portion.
[0068] When the separation layer contains a water-soluble resin, the content of the water-soluble resin is preferably 50 parts by weight or more, more preferably 80 parts by weight or more, and even more preferably 90 parts by weight or more per 100 parts by weight of the separation layer. In one embodiment, the separation layer is composed solely of the water-soluble resin.
[0069] In one embodiment, the separation layer comprises a resin having a cross-linked structure. By using a resin having a cross-linked structure, heat resistance, solubility, etc. can be preferably controlled. The resin having a cross-linked structure can be formed, for example, by film formation under conditions that allow a main agent (polymer) having amino groups, carboxyl groups, hydroxyl groups, etc. to react with a cross-linking agent. The resin having a cross-linked structure is preferably alcohol-soluble or water-soluble.
[0070] The thickness of the release layer is preferably 0.01 μm to 5 μm, more preferably 0.1 μm to 3 μm, and even more preferably 0.5 μm to 2 μm. Within this range, a PSA sheet can be obtained that maintains the adhesiveness of the PSA layer and exhibits good releasability.
[0071] E. Method for manufacturing adhesive sheet
[0072] The above-mentioned adhesive sheet can be manufactured by any appropriate method. The adhesive sheet can be obtained by, for example, coating (applying and drying) a separation layer forming composition on a substrate and forming a separation layer, and then coating an adhesive on the separation layer to form an adhesive layer. The adhesive layer can also be formed by transferring the adhesive layer formed on another substrate to the separation layer. In addition, the adhesive layer can also be formed on a release liner, and the adhesive layer with a release liner can be configured on the separation layer to obtain the adhesive sheet.
[0073] The separation layer-forming composition may be, for example, a resin solution containing an alcohol-soluble resin or a water-soluble resin and any appropriate solvent.
[0074] As the coating method, various methods such as bar coating, air knife coating, gravure coating, gravure reverse coating, reverse roll coating, lip coating, die coating, dip coating, offset printing, flexographic printing, and screen printing can be used.
[0075] F. Recycling Method of Adhesive Sheets
[0076] A method for recycling an adhesive sheet according to an embodiment of the present invention includes impregnating an adhesive sheet, such as the above-described adhesive sheet, with an alcohol solution (e.g., having an alcohol content of 50% by weight or greater), wherein the adhesive sheet comprises an adhesive layer containing an alcohol-soluble resin. In another embodiment, the method for recycling an adhesive sheet, such as the above-described adhesive sheet, comprising an adhesive layer containing a water-soluble resin, includes impregnating an aqueous solution (e.g., having a water content of 50% by weight or greater). The alcohol solution may be 100% alcohol, and the aqueous solution may be 100% water.
[0077] According to the above recycling method, the substrate and the adhesive layer can be separated, and the substrate and / or the adhesive can be reused. The above recycling method is advantageous in that the elements can be reused through a simple and safe operation.
[0078] In one embodiment, the time required to separate the substrate and the adhesive layer is within 10 minutes, preferably within 5 minutes. Within this range, a highly efficient recycling method can be provided. Furthermore, the degree of process flexibility is increased, enabling reductions in energy usage, costs, and CO2 emissions.
[0079] In one embodiment, the temperature of the solvent (alcoholic or aqueous solution) in which the adhesive sheet is immersed is set to 90°C or lower, preferably 60°C or lower. This range provides a highly efficient recycling method. Furthermore, the degree of process flexibility is increased, enabling reductions in energy usage, costs, and CO2 emissions.
[0080] In one embodiment, the amount of the alcohol solution used is set to a weight less than the weight of the adhesive sheet, preferably less than (adhesive sheet weight x 0.8). Furthermore, the amount of water used is set to a weight less than the weight of the adhesive sheet, preferably less than (adhesive sheet weight x 0.8). Within this range, a highly efficient recycling method can be provided. Furthermore, the degree of process freedom is increased, enabling reductions in energy usage, costs, and CO2 emissions.
[0081] Examples of the alcohol include methanol, ethanol, and isopropyl alcohol. In one embodiment, the pKa of the alcohol is preferably 10-20, more preferably 14-18.
[0082] Example
[0083] The present invention will be described in detail below by way of examples, but the present invention is not limited to these examples. The test and evaluation methods in the examples are as follows. In addition, unless otherwise specified, "parts" and "%" are by weight.
[0084] [Production Example 1]
[0085] In a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirring device, 49 parts by weight of 2-ethylhexyl acrylate, 49 parts by weight of butyl methacrylate, 2 parts by weight of acrylic acid, 0.1 parts by weight of 2,2'-azobis(2-amidinopropane) dihydrochloride as a polymerization initiator, 2.0 parts by weight of polyoxyethylene nonylphenyl ether ammonium salt as an emulsifier, and 100 parts by weight of water were charged to carry out emulsion polymerization. The pH was adjusted to 8 with 10% by weight ammonia water to obtain a water-dispersible acrylic polymer I.
[0086] 0.5 parts by weight of an epoxy crosslinking agent (manufactured by Nagase ChemteX Corporation, trade name "EX-313") and 0.5 parts by weight of a tackifier (manufactured by ADEKA Corporation, trade name "UH450-VF") were mixed with 100 parts by weight of the solid content of the water-dispersible acrylic polymer I to obtain a water-dispersible acrylic adhesive (I).
[0087] [Production Example 2]
[0088] 100 parts by weight of 2-hydroxyethyl acrylate and 4 parts by weight of hydroxyethyl acrylate were mixed to prepare a monomer composition.
[0089] Next, nitrogen gas was introduced into a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirrer. Under a nitrogen atmosphere, 163 parts by weight of ethyl acetate, 104 parts by weight of the above-mentioned monomer composition, and 0.2 parts by weight of azobisisobutyronitrile (AIBN) were added, and the mixture was stirred at 60°C for 4 hours to obtain an acrylic polymer solution containing an acrylic polymer II having a weight-average molecular weight of 550,000.
[0090] 4 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE HX") were mixed with 100 parts by weight of the acrylic polymer solution containing the acrylic polymer II to obtain an acrylic adhesive (II).
[0091] [Example 1]
[0092] A 5 wt% methanol solution of an alcohol-soluble resin (copolymer nylon, manufactured by ARKEMA, trade name "Platamid M1276") was applied to a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10, thickness: 100 μm) using a rod coater, and then heated at 140°C for 1 minute to form a separation layer with a thickness of 0.25 μm.
[0093] The water-dispersible acrylic adhesive (I) was applied to the release layer surface, and then heated at 70° C. for 3 minutes to form an adhesive layer having a thickness of 13 μm.
[0094] A PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) was laminated on the adhesive layer to obtain an adhesive sheet (1) comprising substrate / separating layer / adhesive layer / PET release liner.
[0095] [Example 2]
[0096] A PSA sheet was obtained in the same manner as in Example 1 except that a 5 wt % methanol solution of an alcohol-soluble resin (co-nylon, manufactured by ARKEMA, trade name "Platamid M1276") was used instead of a 5 wt % methanol solution of an alcohol-soluble resin (co-nylon, manufactured by ARKEMA, trade name "Platamid H2519").
[0097] [Example 3]
[0098] A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 1 except that a 5 wt % methanol solution of an alcohol-soluble resin (nylon copolymer, manufactured by ARKEMA under the trade name "Platamid M1276") was used instead of a 5 wt % methanol solution of an alcohol-soluble resin (nylon 6 containing methoxymethyl groups, manufactured by VIZI Corporation under the trade name "Fine Resin FR-105").
[0099] [Example 4]
[0100] One surface of a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10", thickness: 100 μm) was subjected to corona treatment (treatment speed: 3 m / min, treatment intensity: 100 W·min / m 2 A 5 wt% methanol solution of an alcohol-soluble resin (copolymer nylon, manufactured by ARKEMA, trade name "Platamid M995") was applied to the corona-treated surface of the substrate using a bar coater, and then heated at 140°C for 1 minute to form a separation layer with a thickness of 0.25 μm.
[0101] The water-dispersible acrylic adhesive (I) was applied to the release layer surface, and then heated at 70° C. for 3 minutes to form an adhesive layer having a thickness of 13 μm.
[0102] A PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) was laminated on the PSA layer to obtain a PSA sheet consisting of substrate / separating layer / PSA layer / PET release liner.
[0103] [Example 5]
[0104] A 5 wt% methanol solution of an alcohol-soluble resin (copolymer nylon, manufactured by ARKEMA, trade name "Platamid H2519") was applied to a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10, thickness: 100 μm) using a rod coater, and then heated at 140°C for 1 minute to form a separation layer with a thickness of 0.25 μm.
[0105] The acrylic adhesive (II) was applied to the release layer surface, and then heated at 130° C. for 1 minute to form an adhesive layer having a thickness of 13 μm.
[0106] A PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) was laminated on the PSA layer to obtain a PSA sheet consisting of substrate / separating layer / PSA layer / PET release liner.
[0107] [Example 6]
[0108] One surface of a substrate (PP substrate, manufactured by Toray Industries, Ltd., trade name "TORAYFAN #60-2500", thickness: 60 μm) was subjected to corona treatment (treatment speed: 3 m / min, treatment intensity: 100 W·min / m 2A 5 wt% methanol solution of an alcohol-soluble resin (copolymer nylon, manufactured by ARKEMA, trade name "Platamid H2519") was applied to the corona-treated surface of the substrate using a bar coater, and then heated at 100°C for 1 minute to form a separation layer with a thickness of 0.25 μm.
[0109] The water-dispersible acrylic adhesive (I) was applied to the silicone-treated surface of a PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) and then heated at 70°C for 3 minutes to form a 13 μm thick adhesive layer.
[0110] A PSA layer with a PET release liner was bonded to the release layer of the substrate to obtain a PSA sheet comprising substrate / release layer / PSA layer / PET release liner.
[0111] [Example 7]
[0112] A 5 wt% methanol solution of an alcohol-soluble resin (copolymer nylon, manufactured by ARKEMA, trade name "Platamid H2519") was applied to a substrate (PO substrate, manufactured by Okura Industries, Ltd., trade name "ODZ-V", thickness: 80 μm) using a rod coater, and then heated at 100°C for 1 minute to form a separation layer with a thickness of 0.25 μm.
[0113] The water-dispersible acrylic adhesive (I) was applied to the silicone-treated surface of a PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) and then heated at 70°C for 3 minutes to form a 13 μm thick adhesive layer.
[0114] A PSA layer with a PET release liner was bonded to the release layer of the substrate to obtain a PSA sheet comprising substrate / release layer / PSA layer / PET release liner.
[0115] [Example 8]
[0116] A 7.5 wt% methanol solution of an alcohol-soluble resin (aminoethylated acrylic polymer, manufactured by Nippon Shokubai Co., Ltd., trade name "Polyment NK-380") was applied to a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10, thickness: 100 μm) using a bar coater. The substrate was then heated at 140°C for 1 minute to form a separation layer with a thickness of 0.4 μm.
[0117] The above-mentioned water-dispersible acrylic adhesive (I) was applied to the release layer surface, and then heated at 70° C. for 3 minutes to form an adhesive layer having a thickness of 13 μm.
[0118] A PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) was laminated on the PSA layer to obtain a PSA sheet consisting of substrate / separating layer / PSA layer / PET release liner.
[0119] [Example 9]
[0120] One surface of a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10", thickness: 100 μm) was subjected to corona treatment (treatment speed: 3 m / min, treatment intensity: 100 W·min / m 2 The corona-treated surface of the substrate was coated with a 5 wt% methanol solution of an alcohol-soluble resin (co-nylon, manufactured by Toray Industries, Ltd., trade name "Amilan CM4000") comprising 100 parts by weight of the alcohol-soluble resin and 10 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "Tetrad-c") using a bar coater. The coating was then heated at 140° C. for 1 minute to form a separation layer having a thickness of 0.25 μm.
[0121] The water-dispersible acrylic adhesive (I) was applied to the release layer surface, and then heated at 70° C. for 3 minutes to form an adhesive layer having a thickness of 13 μm.
[0122] A PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) was laminated on the PSA layer to obtain a PSA sheet consisting of substrate / separating layer / PSA layer / PET release liner.
[0123] [Example 10]
[0124] One surface of a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10", thickness: 100 μm) was subjected to corona treatment (treatment speed: 3 m / min, treatment intensity: 100 W·min / m 2 The corona-treated surface of the substrate was coated with a 5 wt% methanol solution of an alcohol-soluble resin (co-nylon, manufactured by ARKEMA under the trade name "Platamid H2519"), comprising 100 parts by weight of the alcohol-soluble resin and 5 parts by weight of a carbodiimide-based crosslinking agent (manufactured by Nisshinbo Chemical Inc. under the trade name "CARBODILITE V-02"), using a bar coater. The resulting mixture was then heated at 140°C for 1 minute to form a separation layer having a thickness of 0.25 μm.
[0125] The water-dispersible acrylic adhesive (I) was applied to the release layer surface, and then heated at 70° C. for 3 minutes to form an adhesive layer having a thickness of 13 μm.
[0126] A PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) was laminated on the PSA layer to obtain a PSA sheet consisting of substrate / separating layer / PSA layer / PET release liner.
[0127] [Example 11]
[0128] A pressure-sensitive adhesive sheet was obtained in the same manner as in Example 2.
[0129] [Example 12]
[0130] A 10 wt% methanol solution of a water-soluble polymer containing an oxazoline group (Nippon Shokubai, trade name "WS-500") was applied to a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10, thickness: 100 μm) using a rod coater. The substrate was then heated at 140°C for 1 minute to form a separation layer with a thickness of 0.5 μm.
[0131] The water-dispersible acrylic adhesive (I) was applied to the silicone-treated surface of a PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) and then heated at 70°C for 3 minutes to form a 13 μm thick adhesive layer.
[0132] A PSA layer with a PET release liner was bonded to the release layer of the substrate to obtain a PSA sheet comprising substrate / release layer / PSA layer / PET release liner.
[0133] [Example 13]
[0134] One surface of a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10", thickness: 100 μm) was subjected to corona treatment (treatment speed: 3 m / min, treatment intensity: 100 W·min / m 2 A 2.5 wt% methanol solution of a water-soluble resin (polyvinyl pyrrolidone, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., trade name "PITZCOL K-90") was applied to the corona-treated surface of the substrate using a bar coater, and then heated at 140°C for 1 minute to form a separation layer with a thickness of 0.1 μm.
[0135] The water-dispersible acrylic adhesive (I) was applied to the silicone-treated surface of a PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) and then heated at 70°C for 3 minutes to form a 13 μm thick adhesive layer.
[0136] A PSA layer with a PET release liner was bonded to the release layer of the substrate to obtain a PSA sheet comprising substrate / release layer / PSA layer / PET release liner.
[0137] [Example 14]
[0138] One surface of a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10", thickness: 100 μm) was subjected to corona treatment (treatment speed: 3 m / min, treatment intensity: 100 W·min / m 2 A 2.5 wt% methanol solution of an alcohol-soluble resin (polyvinyl butyral, manufactured by Kuraray Co., Ltd., trade name "Mowtial B60T") was applied to the corona-treated surface of the substrate using a bar coater, and then heated at 140°C for 1 minute to form a separation layer with a thickness of 0.1 μm.
[0139] The water-dispersible acrylic adhesive (I) was applied to the silicone-treated surface of a PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) and then heated at 70°C for 3 minutes to form a 13 μm thick adhesive layer.
[0140] A PSA layer with a PET release liner was bonded to the release layer of the substrate to obtain a PSA sheet comprising substrate / release layer / PSA layer / PET release liner.
[0141] [Example 15]
[0142] One surface of a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10", thickness: 100 μm) was subjected to corona treatment (treatment speed: 3 m / min, treatment intensity: 100 W·min / m 2 A 5 wt% methanol solution of a water-soluble resin (polyvinyl alcohol resin, manufactured by Mitsubishi Chemical Corporation, trade name "Gohsenol KL-05") was applied to the corona-treated surface of the substrate using a bar coater, and then heated at 140°C for 1 minute to form a separation layer with a thickness of 0.25 μm.
[0143] The water-dispersible acrylic adhesive (I) was applied to the silicone-treated surface of a PET release liner (Mitsubishi Chemical Corporation, trade name "MRF38", thickness: 38 μm) and then heated at 70°C for 3 minutes to form a 13 μm thick adhesive layer.
[0144] A PSA layer with a PET release liner was bonded to the release layer of the substrate to obtain a PSA sheet comprising substrate / release layer / PSA layer / PET release liner.
[0145] [Comparative Example 1]
[0146] A water-dispersible acrylic adhesive (I) was applied to a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10", thickness: 100 μm) and then heated at 70° C. for 3 minutes to form a 13 μm thick adhesive layer.
[0147] A PET release liner (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation, thickness: 38 μm) was laminated on the PSA layer to obtain a PSA sheet consisting of substrate / PSA layer / PET release liner.
[0148] [Comparative Example 2]
[0149] One surface of a substrate (PET substrate, manufactured by Toray Industries, Ltd., trade name "Lumirror #100-S10", thickness: 100 μm) was subjected to corona treatment (treatment speed: 3 m / min, treatment intensity: 100 W·min / m 2 The corona-treated surface of the substrate was coated with a water-dispersible acrylic adhesive (I), and then heated at 70° C. for 3 minutes to form an adhesive layer having a thickness of 13 μm.
[0150] A PET release liner (trade name "MRF38", manufactured by Mitsubishi Chemical Corporation, thickness: 38 μm) was laminated on the PSA layer to obtain a PSA sheet consisting of substrate / PSA layer / PET release liner.
[0151] <Evaluation>
[0152] After peeling the release liner from the PSA sheets obtained in Examples and Comparative Examples, the PSA sheets were subjected to the following evaluations. The results are shown in Table 1.
[0153] (1) Recyclability
[0154] At a predetermined temperature and a predetermined amount of alcohol or water listed in the table, an adhesive sheet having the same weight as the alcohol / water was added, and the separation behavior between the adhesive layer and the substrate layer was visually observed.
[0155] The case where the adhesive layer and the base material layer separated within 60 minutes was evaluated as acceptable (◯), and the case where no separation occurred was evaluated as unacceptable (×).
[0156] (2) Anchoring force
[0157] A double-sided adhesive tape (manufactured by Nitto Denko Corporation, trade name "No. 5000N") was bonded to the substrate of the adhesive sheet and fixed to SUS304.
[0158] A single-sided adhesive tape (trade name "No. 315" manufactured by Nitto Denko Corporation) was pressure-bonded to the adhesive layer of the adhesive sheet by reciprocating a 2 kg roller once, and the mixture was allowed to stand at 23°C / 50% RH for 30 minutes.
[0159] The single-sided adhesive tape (No. 315) was peeled using a tensile testing machine (manufactured by Shimadzu Corporation, trade name "AGS-50NX") at a peel angle of 180°, a peel speed (tensile speed) of 300 mm / min, and a measurement temperature of 23°C. If there was a site of peeling between the adhesive layer and the base layer or the separator, it was recorded as anchor failure, and the peel force (N / 20 mm) at that site was referred to as the anchor force A. If there was no anchor failure site and the single-sided adhesive tape (No. 315) was peeled from the adhesive layer, it was recorded as interfacial failure, and the peel force (N / 20 mm) was referred to as the anchor force A.
[0160] In addition, a sample piece was obtained in the same manner as in each experimental example except that no separation layer was formed in each of the examples and comparative examples, and the anchoring force B of the sample piece was measured by the above-mentioned method.
[0161] The cases where the ratio of the anchoring force A to the anchoring force B was 0.5 or more and the ratio of the anchoring force B to the adhesive force A was 2 or more were evaluated as acceptable (○), and the other cases were evaluated as unacceptable (×).
[0162] (3) Water resistance
[0163] A double-sided adhesive tape (manufactured by Nitto Denko Corporation, trade name "No. 5000N") was bonded to the substrate of the adhesive sheet and fixed to SUS304.
[0164] A single-sided adhesive tape (Nitto Denko Corporation, trade name "No. 315") was pressure-bonded to the adhesive layer of the adhesive sheet by moving a 2 kg roller back and forth once, and the sample was left to stand at 23°C / 50% RH for at least 30 minutes. The sample was then immersed in water for 30 minutes.
[0165] The anchoring force of the PSA sheet after immersion in water was measured by the same method as the above-mentioned anchoring force measurement, and this was defined as the anchoring force C after immersion in water.
[0166] The case where the ratio of the anchoring force B to the anchoring force C was 0.5 or more was evaluated as acceptable (○), and the other cases were evaluated as unacceptable (×).
[0167] (4) Adhesion
[0168] The adhesive layer of the adhesive sheet was bonded to SUS304 by moving a 2 kg roller back and forth once. The adhesive strength was measured according to JIS Z0237:2000 (peel angle 180°, peel speed (tensile speed) 300 mm / min, measurement temperature: 23°C).
[0169] In addition, a sample sheet was obtained in the same manner as in each experimental example except that no separation layer was formed in each of the examples and comparative examples. The adhesive strength B of the sample sheet was measured by the above-mentioned method.
[0170] (5) Reusability
[0171] After the recyclability evaluation, 0.2 g of the dried substrate (PET film) was dissolved in 50 mL of a phenol / 1,1,2,2-tetrachloroethane mixed solvent (weight ratio 60 / 40) at 135°C for 30 minutes. The intrinsic viscosity (IV value) of the resulting solution at 30°C was measured using a <Measurement Apparatus: Constant Temperature Bath TV-5S for Kinematic Viscosity Measurement (manufactured by Thomas Kagaku Co., Ltd.) and a viscometer: Ubbelohde Viscometer (No. 1C)> according to JIS K7390:2003. An intrinsic viscosity of 0.5 dL / g or higher was considered acceptable (○), while an intrinsic viscosity of less than 0.5 dL / g was considered unacceptable (×).
[0172] [Table 1]
[0173]
[0174] Description of Reference Numerals
[0175] 10 Adhesive layer
[0176] 20 separation layer
[0177] 30 substrate
[0178] 100 adhesive sheets
Claims
1. A pressure-sensitive adhesive sheet comprising, in this order: a pressure-sensitive adhesive layer, a release layer, and a base material formed of a resin; The separation layer is composed of an alcohol-soluble resin or a water-soluble resin.
2. The adhesive sheet according to claim 1, wherein The adhesive sheet has an anchoring force A of 1 N / 20 mm or more.
3. The adhesive sheet according to claim 1, wherein The ratio of the anchoring force A of the PSA sheet to the adhesive force A of the PSA sheet is 2 or greater.
4. The adhesive sheet according to claim 1, wherein The ratio of the anchoring force A of the pressure-sensitive adhesive sheet to the anchoring force B of a sample sheet formed without the separation layer is 0.5 or more.
5. The adhesive sheet according to claim 1, wherein The adhesive sheet had an anchoring force C of 1 N / 20 mm or greater after being immersed in water at 23° C. for 30 minutes. The adhesive sheet according to claim 1 , wherein The ratio of the anchoring force C after the PSA sheet is immersed in water at 23° C. for 30 minutes to the anchoring force A of the PSA sheet is 0.5 or more.
7. The adhesive sheet according to claim 1, wherein The adhesive force A of the adhesive sheet is 0.7 or more relative to the adhesive force B of a sample sheet formed without the separation layer.
8. The adhesive sheet according to claim 1, wherein The separation layer is composed of an alcohol-soluble resin.
9. The adhesive sheet according to claim 1 or 8, wherein The alcohol-soluble resin is a polyamide resin, an aminoethylated polymer resin, a polyvinyl butyral resin, a polyvinyl pyrrolidone resin or an oxazoline-containing polymer resin.
10. The adhesive sheet according to claim 1, wherein The separation layer includes a resin having a cross-linked structure.
11. The adhesive sheet according to claim 1, wherein The thickness of the separation layer is 0.01 μm to 5 μm.
12. The adhesive sheet according to claim 1, wherein The substrate is composed of a polyester resin or a polyolefin resin.
13. The adhesive sheet according to claim 1, wherein The substrate is a substrate subjected to surface treatment.
14. The adhesive sheet according to claim 1, wherein The adhesive layer includes an acrylic adhesive.
15. The adhesive sheet according to claim 1, wherein The adhesive layer includes an emulsion-based adhesive.
16. The adhesive sheet according to claim 1, wherein The adhesive layer is separated from the substrate using a solvent capable of dissolving the resin constituting the separation layer.
17. A method for recycling an adhesive sheet, comprising: An alcohol solution is impregnated into a pressure-sensitive adhesive sheet according to claim 1 , wherein the pressure-sensitive adhesive sheet comprises a pressure-sensitive adhesive layer containing an alcohol-soluble resin. 18 . A method for recycling a PSA sheet, comprising impregnating a PSA sheet according to claim 1 and comprising impregnating the PSA sheet with an aqueous solution.
19. A laminate comprising a functional layer, a separation layer, and a substrate in this order, The separation layer is composed of an alcohol-soluble resin.
Citation Information
Patent Citations
Method for removing functional layer from laminated polyester film
JP2022130226A